A Systematic Review and Meta-analysis of Thrombotic Events Following Endovenous Thermal Ablation of the Great Saphenous Vein. (September 2018) - Healy, Donagh A.; Kimura, Shiori; Power, David; Elhaj, Abubaker; Abdeldaim, Yasser; Cross, Keith S.; McGreal, Gerard T.; Burke, Paul E.; Moloney, Tony; Manning, Brian J.; Kavanagh, Eamon G.
Abstract : Objectives: A systematic review and meta-analysis was performed to determine the incidence of thrombotic events following great saphenous vein (GSV) endovenous thermal ablation (EVTA). Methods: MEDLINE, Embase and conference abstracts were searched. Eligible studies were randomised controlled trials and case series that included at least 100 patients who underwent GSV EVTA (laser ablation or radiofrequency ablation [RFA]) with duplex ultrasound (DUS) within 30 days. The systematic review focused on the complications of endovenous heat induced thrombosis (EHIT), deep venous thrombosis (DVT), and pulmonary embolism (PE). The primary outcome for the meta-analysis was deep venous thrombotic events which were defined as DVT or EHIT Type 2, 3, or 4. Secondary outcomes for the meta-analysis were EHIT Type 2, 3, or 4, DVT and PE. Subgroup analyses were performed for both the RFA and EVLA groups. Pooled proportions were calculated using random effects modelling. Results: Fifty-two studies (16, 398 patients) were included. Thrombotic complications occurred infrequently. Deep venous thrombotic events occurred in 1.7% of cases (95% CI 0.9–2.7%) (25 studies; 10, 012 patients; 274 events). EHIT Type 2, 3, or 4 occurred in 1.4% of cases (95% CI 0.8–2.3%) (26 studies; 10, 225 patients; 249 events). DVT occurred in 0.3% of cases (95% CI = 0.2%–0.5%) (49 studies; 15, 676 patients; 48 events). PE occurred in 0.1% of cases (95% CI = 0.1–0.2%) (29 studies; 8223 patients; 3 events). Similar results were found when the RFA and EVLA groups were analysed separately. Conclusion: Thrombotic events occur infrequently following GSV EVTA. Given the large numbers of procedures worldwide and the potential for serious consequences, further research is needed on the burden of these complications and their management.